Pendampingan Pembuatan Copy and Content Writing untuk Meningkatkan Branding Lembongan Mantra Huts melalui Digital Marketing - I Wayan Ana; I Made Suniastha Amertha; Made Susini (Warmadewa Press, 2025)
This Community Service Program (PkM) was conducted to address three main challenges faced by Lembongan Mantra Huts: (1) how to improve visibility and attractiveness through social media, (2) identifying the most effective digital platforms for promotion, and (3) designing suitable content strategies to attract both domestic and international tourists. The method employed was a participatory mentoring approach through training in copywriting, designing a content calendar, and optimizing the use of digital platforms such as Instagram, Facebook, and Google Business Profile. The results indicate that consistent use of visual content and guest experience narratives significantly increased audience engagement. Instagram was found to be the most effective platform to reach international tourists, Facebook was more relevant to the domestic market, and Google Business Profile enhanced discoverability in online searches. Content strategies focusing on storytelling, practical information, and value-added promotions played a crucial role in strengthening the property’s branding. The conclusion highlights that well-directed social media management, tailored to audience needs, successfully improved the digital image and competitiveness of Lembongan Mantra Huts, reinforcing its position as an attractive tourism destination in Nusa Lembongan.